Foreign direct investment and it’s prospects in Nepal - Sapkota, Rajan (Chaitanya Research Journal, 2024)
This article delves into the landscape of Foreign Direct Investment (FDI) in Nepal, examining its historical development, sectoral trends, and the legal framework governing foreign investments. It highlights the key sectors that have attracted substantial FDI, such as hydropower, tourism, agriculture, and information technology, while also addressing the challenges that have impeded growth, including regulatory hurdles and infrastructural limitations. Additionally, the article explores Nepal's efforts to reform policies and create a more favorable investment climate, positioning the country as an attractive destination for foreign investors. The research further outlines the potential economic and social benefits of FDI in promoting sustainable development and inclusive growth, while analyzing the opportunities available considering the nation's untapped resources and strategic geographical location. Ultimately, the article aims to provide a comprehensive understanding of how FDI can contribute to Nepal’s long-term economic prosperity and its integration into the global economy.